IDENTIFICATION AND DRUG-RESISTANCE OF CLICAL ISOLATES IN GUNMA PREFECTURE IN 1989 - TANAKA, TOKUMITSU (Kita Kantō igaku (The Kitakanto Medical Journal), 1990)
1) The isolation frequency of clinical pathogen and their drug-resistances were surveyed by 8 public hospitals in Gunma Prefecture in Japan in 1989. 15604 strains were identified and 16942 strains were examined for 22 kinds of drug-resistances. 2) Among clinical isolates, 47% were Gram-negative rods and 42% were Gram-positive cocci. S. aureus (13.2%), E. coli (7.9%), P. aeruginosa (8.8%), and coagulase-negative staphylococci (8.1%) were the major bacterial species. Isolation frequency of these isolates were different in different clinical sources and in different hospitals. 3) Seventeen kind of species whose isolation frequency was more than 1 % were surveyed for their drug-resistances. Both the 3rd-generation cephems and new quinolones were losing their antibacterial effect, especially in Pseudomonas and S. aureus. 4) Identified species were different between inpatients and outpatients. Development of drug-resistances is more marked in inpatients than in out-patients. In some case hospital infections were suggested.